Aplicação da modelagem de processos com a notação BPMN em uma empresa do ramo alimentício - Lira, Igor Leonardo Nogueira de (Universidade Federal Rural do Semi-Árido, 2018)
The priority of companies must always be related to the customers satisfaction. In order to achieve this, it is necessary to be concerned with each process in the organization, since each of them has its impact on the service offered to the client. Consequently the lack of attention to the processes and a bad harmony with the organization of the physical space can generate failures, increasing costs, expenses and customer dissatisfaction. The research was conducted through a case study, based on the technical visits and individual interviews. Therefore, the objective of this article is to analyze the processes involved and propose improvements in a retail food company. One of the means of achieving satisfactory results it is by the representation of the layout, with the presence of analysis and modeling of the processes through the standard BPMN (Business Process Modeling Notation) language. Through the application of these resources, the identification of critical points becomes viable. The results obtained provides corrections to the flaws presented by the interaction routine between clients and employees, therefore providing a better space for attendance to the services offered and for the client’s flow.
Artigo Acadêmico
Keywords: Modelagem de processos; BPMN; Layout; Fluxo; Business process modeling; BPMN; Layout; Client’s flow; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA